Experimental study reading of medicine package insert, for Braille System transcript, to the blind users - Lopes, Maria Olinda; Spinillo, Carla Galvão (InfoDesign, 2008)
This paper pretends the description of an experimental study realized with blind users. They read the transcription of the insert to the Braille System. For that reading did develop an interview with the Karel van der Waarde framework of graphic presentation application. The objective is the evaluation of the medicine package insert in to the graphic and informational characteristics for blind people users.